THE TRIPOLAR TYPOLOGY OF RELIGION: FOSTERING MODERATION, HARMONY AND RESILIENCE IN THE GLOBALIZATION ERA - Lestari, Rizki Dwi; Syuhud, Syuhud (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Amidst the diversity of ethnicities, cultures, and religions, conflicts often arise due to extremists who claim to possess absolute truth. Alan Race’s Tripolar Typology of Religion categorizes religious perspectives into three types: exclusivism, inclusivism, and pluralism. Rigid exclusivism frequently triggers conflicts, whereas the more open approaches of inclusivism and pluralism promote tolerance and interreligious dialogue. This research aims to describe these three typologies and introduce religious moderation as a response to existing divisions. The study employs a qualitative approach, utilizing a literature review as its primary research method. Data collection techniques involve descriptive-analytic methods, including reading, understanding, reviewing, and analyzing relevant literature. The findings reveal that the typology of religion, religion itself, and globalization are deeply interconnected in shaping the contemporary religious landscape. Understanding these three concepts is essential for comprehending the dynamics of religion in the context of diversity and the challenges posed by globalization. Religion in the age of globalization faces complex issues such as extremism, radicalism, and modernization. Religious moderation emerges as a balanced response to these challenges, offering a middle ground that harmonizes the interpretation of religious texts with universal human values. A comprehensive understanding of the typology of religion, the interplay between religion and globalization, and the principles of religious moderation is crucial for fostering a more peaceful and tolerant world. By respecting differences and upholding shared human values, we can work towards creating a better future for all